Preoperative Assessment of Patients Undergoing Elective Gastrointestinal Surgery: Does Body Mass Index Matter? - Sivesh K. Kamarajah; Mustafa Sowida; Amirul Adlan; Behrad Barmayehvar; Christina Reihill; Parvez Ellahee (Journal of Obesity)
Background. At Queen Elizabeth Hospital Birmingham (QEHB), no specific protocol to stratify patients by body mass index (BMI) exists. This study sought to evaluate outcomes following gastrointestinal surgery. Methods. Patients undergoing gastrointestinal surgery attending preassessment screening clinic (PAS) from August to September 2016 at the QEHB were identified. Primary outcome was postoperative complications. Secondary outcomes were major complications and 30-day readmission rates. Results. Of 368 patients preassessed, 31% (116/368) were overweight and 35% (130/368) were obese. Median age was 57 (range: 17–93). There was no difference of BMI between the low risk and high risk clinics. Patients in high risk clinic had significantly higher rates of comorbidities, major surgical grades, and malignancy as the indication for surgery. Overall complication rates were 14% (52/368), with 3% (10/368) having major complications (Clavien-Dindo Grades III-IV). Whilst BMI was associated with comorbidity (p=0.03) and ASA grade (p<0.001), it was not associated with worse outcomes. Patients attending high risk clinic had significantly higher rates of complications. Conclusions. Surgery grade was found to be an independent risk factor of complication rates. Use of BMI as an independent factor for preassessment level is not justified from our cohort.